CP-038 Adequacy of nutrition energy delivery in surgical intensive care. (24th March 2015) - Jolly, C; Raffy, F; Audibert, G; Perrier, J; Quilliot, D
Abstract : Background: Underfeeding is correlated with a higher morbidity rate, mortality and lenght of stay. Measuring and managinig nutrional risk are therefore important tasks. Purpose: Evaluation of nutrition adequacy energy delivery in surgical intensive care unit (ICU), compliant with European recommendations. Material and methods: Prospective study, of one month, in 3 surgical ICU with daily analysis of all nutritional supports. Were taken into account:oral alimentation and enrichment, enteral and parenteral nutrition, micronutrients and electrolytes supplies, energy delivery data and adequacy of nutritional support, duration, indication, weight loss. Energy targets were set at 15 kcal/kg/day for Day 3 (D3) and 20 kcal/kg/day for D7. Kruskal Wallis and Fischer tests were used for values of p < 0.05 considered significant ones. Results: Sixty six patients: mean age 57.9 ± 17.3 years and mean BMI 26.9 ± 5.2 kg/m 2 . Mean of length of stay was 10.1 ± 5.3 days (p > 0.05). Nutrition was initiated with parenteral nutrition for 39.4% patients versus 37.9% with enteral nutrition versus 22.7% with oral nutrition (p < 0.01). Time to feeding was 2.2 ± 1.1 days (p > 0.05). Energy target was reached at D3 for 53% patients vs 62% at D7 (p > 0.05). Time needed to achieve the target rate was 5.3 ± 2.9 days (p > 0.05). Energy delivery was lower than the energy target during the first 3 days (p < 0.001). Difference between energy target and delivery decreased from −19.7 kcal/kg/day as a mean during the first day, to a mean of −3.3 kcal/kg/day at D7. Proportion of energy target provided by the enteral, parenteral or oral route was not significantly different from D1 to D7 (p > 0.05). Cumulated energy balance was 5023 ± 38.9 kcal/kg/day. At the last day, protein intake was <1.2 g/kg/day for 32% of patients receiving parenteral nutrition vs. 38.5% receiving enteral nutrition (p < 0.05). Conclusion: One can reach the caloric target at D3 and D7 and provide a better balance between enteral and parental nutrition as defined by European recommendations. References and/or Acknowledgements: ESPEN guidelines 2006/2009 No conflict of interest.